Bored Pile Foundation Planning for 7 Level Story Low-Rise Apartment in Silty Clay Soil in Cakung Area East Jakarta - Ivana Vianca; Yusra Aulia Sari (Journal of Civil Engineering and Planning (JCEP), 2023)
The lower structure has a role to maintain the stability of the structure of the building and is the most vital thing in building planning. The substructure itself is one of the foundations. Foundation is defined as the lowest part of the building that functions to transmit the load of the building to the soil or rocks below it. The purpose of this research is to plan the pile foundation in the low-rise apartment and plan the required budget. Based on the soil investigation, it was found that the soil type was dominated by silty clay. The foundation is planned to use bored pile with a diameter of 0.7 m with a depth of 20 m on sample bore hole 02 and 15 m on sample bore hole 03. The ultimate axial bearing capacity calculation using the Meyerhof method is obtained at 492.162 tons in bore hole 02 and 677,195 tons in bore hole 03, with a permit axial capacity of 196.865 tons on bore hole 02 and 270,878 tons on bore hole 03. The calculation of single pile settlement using the Semi-Empirical Method is obtained at bore hole 02 of 0.025 m and on bore hole 03 of 0.021 m with an immediate settlement calculation at pile group using the Vesic Method is in the range of 2,946 – 5,140 m. The pile cap design obtained consists of three pile configurations, namely 2, 4 and 8 piles.